Social Entrepreneurship and Social Innovation 2018
DOI: 10.4324/9781351239028-8
|View full text |Cite
|
Sign up to set email alerts
|

The role of stakeholder networks in shaping the development of social enterprise ecosystems

Abstract: This chapter will explore the role of stakeholder and institutional networks in shaping the development of social enterprise ecosystems across Europe. A Weberian view of power is adopted in order to show that dominant stakeholders can distort reality, obscure truth, and create paradigmatic narratives while pursuing their own interests. This chapter will also draw upon biological evolutionary theory, social network theory, and network pluralism to identify a typology of social enterprise ecosystems. This typolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Works that took a critical or analytical approach to social innovation storytelling tended to argue that stories and narratives around social entrepreneurship contain attitudes, beliefs and assumptions that are largely unconscious. These function to gloss over or obfuscate the tensions and contradictions inherent in social entrepreneurship, whether through the power of totalising grand narratives (Dey and Steyaert, 2010;Teasdale et al, 2020), through possible narrative misconduct by dominant players (Hazenberg et al, 2018), a fantasy-laden attachment to legal structures as a source of stability, balance and the resolution of tension (Kenny et al, 2020), potential "greenwashing" in the fashion industry (Bertola et al, 2020), "regulatory hacking" designed to influence local policy (Sharp, 2018) or through the Social enterprise and social innovation suppression and understatement of those tensions in narrations of the social-entrepreneurial self (Jones et al, 2008). This theme of the unconscious motivations, beliefs and attitudes motivating social entrepreneurship is also present in Jones et al's (2008) exploration of the unstated and understated narrative components of social entrepreneurial identity, which they argue are indicative of the avoidance or suppression of important issues and tensions.…”
Section: Social Enterprise and Social Innovationmentioning
confidence: 99%
“…Works that took a critical or analytical approach to social innovation storytelling tended to argue that stories and narratives around social entrepreneurship contain attitudes, beliefs and assumptions that are largely unconscious. These function to gloss over or obfuscate the tensions and contradictions inherent in social entrepreneurship, whether through the power of totalising grand narratives (Dey and Steyaert, 2010;Teasdale et al, 2020), through possible narrative misconduct by dominant players (Hazenberg et al, 2018), a fantasy-laden attachment to legal structures as a source of stability, balance and the resolution of tension (Kenny et al, 2020), potential "greenwashing" in the fashion industry (Bertola et al, 2020), "regulatory hacking" designed to influence local policy (Sharp, 2018) or through the Social enterprise and social innovation suppression and understatement of those tensions in narrations of the social-entrepreneurial self (Jones et al, 2008). This theme of the unconscious motivations, beliefs and attitudes motivating social entrepreneurship is also present in Jones et al's (2008) exploration of the unstated and understated narrative components of social entrepreneurial identity, which they argue are indicative of the avoidance or suppression of important issues and tensions.…”
Section: Social Enterprise and Social Innovationmentioning
confidence: 99%
“…(2018, p. 300–301) Different problems related to enabling ecosystems for SEs exist. For instance, there are inefficient ways to use financial resources, which stand out in projects with high power distance between stakeholders (Hazenberg et al., 2018, p. 116) Thus, financial resources are needed, but they need to be utilised in a way that creates most impact in the society. In addition, financing of the SEs is often centralised to the known actors, and scaling is difficult for smaller SEs.…”
Section: Social Enterprise Ecosystemsmentioning
confidence: 99%
“…In addition, financing of the SEs is often centralised to the known actors, and scaling is difficult for smaller SEs. On the other hand, sometimes small, local actors create a lot of impact within a small area, and act in replacement of the public services (Hazenberg et al., 2018, p. 118–119). Also Mazzucato (2019) has reported that ecosystems for mission oriented business and innovation endeavours need understanding and emphasis on the public sector capabilities, financing mechanisms, and citizen engagement.…”
Section: Social Enterprise Ecosystemsmentioning
confidence: 99%
“…Although the European Commission (2014) and Hazenberg et al (2016a;2016b; explored the fundamental features of the UK social enterprise ecosystem, only the European Commission ( 2014) study disclosed specific stakeholders related to the essential elements of the UK's social enterprise ecosystem. Hazenberg et al (2017) mapped the key stakeholders and the relationship of each stakeholder in the social enterprise ecosystem at national level across the Europe, including the UK (England and Scotland). Referring to those earlier studies, the current study attempts to expose the role of key stakeholders in the social enterprise ecosystem and to summarise the support programmes or activities each stakeholder carries out according to the ecosystem components.…”
Section: Key Players In the Uk's Social Enterprise Ecosystemmentioning
confidence: 99%